Antiretroviral Therapy Helps HIV-Positive Women Navigate Social Expectations for and Clinical Recommendations against Childbearing in Uganda. (18th September 2014) - Kastner, Jasmine; Matthews, Lynn T.; Flavia, Ninsiima; Bajunirwe, Francis; Erikson, Susan; Berry, Nicole S.; Kaida, Angela
Abstract : Understanding factors that influence pregnancy decision-making and experiences among HIV-positive women is important for developing integrated reproductive health and HIV services. Few studies have examined HIV-positive women's navigation through the social and clinical factors that shape experiences of pregnancy in the context of access to antiretroviral therapy (ART). We conducted 25 semistructured interviews with HIV-positive, pregnant women receiving ART in Mbarara, Uganda in 2011 to explore how access to ART shapes pregnancy experiences. Main themes included: (1) clinical counselling about pregnancy is often dissuasive but focuses on the importance of ART adherence once pregnant; (2) accordingly, women demonstrate knowledge about the role of ART adherence in maintaining maternal health and reducing risks of perinatal HIV transmission; (3) this knowledge contributes to personal optimism about pregnancy and childbearing in the context of HIV; and (4) knowledge about and adherence to ART creates opportunities for HIV-positive women to manage normative community and social expectations of childbearing. Access to ART and knowledge of the accompanying lowered risks of mortality, morbidity, and HIV transmission improved experiences of pregnancy and empowered HIV-positive women to discretely manage conflicting social expectations and clinical recommendations regarding childbearing.